Surrogacy agreement: problems of legal regulation - Toilybekova , E.O.; Voronin , M.V.; Ablaeva, E.B. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The purpose of the study is to examine issues arising in the legislation of Kazakhstan and law enforcement practice governing legal relations between the parties to the surrogacy agreement. The theoretical and practical significance of the study lies in the fact that its results can be taken into account by legislators when amending and supplementing legislative acts on healthcare issues, by practitioners when drafting surrogacy agreements, theorists when preparing teaching materials on medical and reproductive law, and citizens when exercising their constitutional right to health protection through the use of surrogacy. The study concludes that the existing difficulties in the application of surrogacy arise, first, from the fact that surrogacy remains outside the scope of comprehensive state legal regulation. Second, to the legal conflicts, gaps, and other defects in the legislation of Kazakhstan regulating the application of assisted reproductive methods and technologies legal conflicts, gaps, and other defects that prevent citizens from exercising their constitutional right to reproductive health, motherhood, and fatherhood, as well as the regulation of legal relations between persons involved in the use of surrogacy. Third, uncertainty or misunderstanding of the procedure itself for fertilizing male and female sex cells outside the human body, the procedure for transferring and implanting a human embryo into a gestational carrier – a third party providing services for carrying a pregnancy and giving birth to children who are genetically unrelated to them – as well as the legal nature and all essential terms of a surrogacy agreement, such as: the main subject and object, the scope of rights and obligations of the parties, and the limits and measures of responsibility of the participants in the process. The reliability of the obtained results is ensured by the chosen methodological basis of the research, which includes a set of general scientific theoretical and special private practical methods of cognition.